2017
DOI: 10.1002/2017ja024276
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of High‐Latitude Geomagnetic Activity in Individual Years

Abstract: We study the seasonal variation of high‐latitude geomagnetic activity in individual years in 1966–2014 (solar cycles 20–24) by identifying the most active and the second most active season based on westward electrojet indices AL (1966–2014) and IL (1995–2014). The annual maximum is found at either equinox in two thirds and at either solstice in one third of the years examined. The traditional two‐equinox maximum pattern is found in roughly one fourth of the years. We found that the seasonal variation of high‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The peak months of all three studied quantities in the declining phase of SC23 occur exclusively in the northern hemisphere winter, while the classic pattern of equinoctial peaks seems more typical in the preceding years. The peak months in both IMF power and ground ULF power closely resemble the ones reported for solar wind in Tanskanen et al (2017).…”
Section: Discussionsupporting
confidence: 78%
“…The peak months of all three studied quantities in the declining phase of SC23 occur exclusively in the northern hemisphere winter, while the classic pattern of equinoctial peaks seems more typical in the preceding years. The peak months in both IMF power and ground ULF power closely resemble the ones reported for solar wind in Tanskanen et al (2017).…”
Section: Discussionsupporting
confidence: 78%
“…Tanskanen et al () studied the seasonal variation of high‐latitude geomagnetic activity in 1995–2014 using the IL index and in 1966–2014 using the AL index. They found that during the past 45 years, only less than one fourth of the individual years follow the classical two‐equinox maximum pattern.…”
Section: Discussionmentioning
confidence: 99%
“…They found enhanced activity in spring and fall when studying multiyear averaged data. Although the two‐equinox pattern in geomagnetic variation is seen in the multiyear averages, only one fourth of the year between 1966 and 2014 show this pattern (Tanskanen et al, ). In addition to large year‐to‐year variability, we found distinct latitudinal differences on seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of geomagnetic activity (Tanskanen et al, 2017) and geomagnetic indices (Campbell, 1979;Lockwood et al, 2017Lockwood et al, , 2018 vary both within and between solar cycles (Tindale & Chapman, 2016. The distributions of solar wind variables can be non-Gaussian (Veselovsky et al, 2010, and references therein).…”
Section: 1029/2018sw001884mentioning
confidence: 99%